Manual of Standardization in the Romance Languages - Lebsanft, Franz; Tacke, Felix (Manuals of romance linguistics ;, 2020)
Language standardization is an ongoing process based on the notions of linguistic correctness and models. This manual contains thirty-six chapters that deal with the theories of linguistic norms and give a comprehensive up-to-date description and analysis of the standardization processes in the Romance languages. The first section presents the essential approaches to the concept of linguistic norm ranging from antiquity to the present, and includes individual chapters on the notion of linguistic norms and correctness in classical grammar and rhetoric, in the Prague School, in the linguistic theory of Eugenio Coseriu, in sociolinguistics as well as in pragmatics, cognitive and discourse linguistics. The second section focuses on the application of these notions with respect to the Romance languages. It examines in detail the normative grammar and the normative dictionary as the reference tools for language codification and modernization of those languages that have a long and well-established written tradition, i.e. Romanian, Italian, French, Catalan, Spanish, and Portuguese. Furthermore, the volume offers a discussion of the key issues regarding the standardization of the 'minor' Romance languages as well as Creoles.